Evaluation of serum vitamin D levels in COVID-19 positive critically ill adults - Ola Alsegai; Kannan Sridharan; Mona Hammad; Mustafa Mohamed Hammad (Pensoft Publishers, 2021)
Background: Contradictory evidence exists regarding the association between serum vitamin D levels and the severity and outcomes in coronavirus 2019 (COVID-19) infected patients. We undertook the present study to evaluate the serum vitamin D levels with the other laboratory biomarkers, and the outcomes in our critically ill patients. Methods: A retrospective observational study was carried out in 58 critically ill adults. Details on their demographics, laboratory parameters such as 25-hydroxy vitamin D [25(OH)D] levels, interleukin-6, serum ferritin, lactate dehydrogenase, creatine kinase (CK), D-dimer, C-reactive protein, fibrinogen, procalcitonin, and erythrocyte sedimentation rate were retrieved. Serum 25(OH)D levels were categorized as follows: ≥50 nmol/L - normal; 30-49 - insufficient; and <30 nmol/L - deficient. Post-hoc, we also compared the outcomes between those with 25(OH)D levels of 80 nmol/L and above, with those of <80 nmol/L. Results: Fifty-eight patients were recruited of which 31 (53.4%) died. Mean ± SD serum 25(OH)D levels amongst the study participants were 48.5 ± 27.7 nmol/L. Twenty-two (37.9%) individuals had insufficient 25(OH)D levels, and 15 (25.9%) were deficient. Eight (13.8%) participants had their serum 25(OH)D levels ≥80 nmol/L. Median (range) 25(OH)D levels were not significantly different between those who died compared to those alive [41 (20-162) vs. 41 (17-86) nmol/L; p = 0.8]. Significantly higher D-dimer levels were observed amongst those with <80 nmol/L serum 25(OH)D levels. No significant differences were observed between 25(OH)D and other laboratory biomarkers except for elevated CK in patients with insufficient 25(OH)D levels. Conclusion: We did not observe any significant differences in the serum 25(OH)D levels amongst our critically ill adults who died and who were alive at the time of their admission.